PEMENUHAN HAK DAN KEWAJIBAN SUAMI ISTRI PADA PASANGAN LONG DISTANCE MARRIAGE: PEMENUHAN HAK DAN KEWAJIBAN SUAMI ISTRI PADA PASANGAN LONG DISTANCE MARRIAGE - Nabilah Falah (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
This paper tries to explain how the fulfillment of the rights and obligations of husband and wife in long-distance married couples, especially for respondents who are in Purwokerto City. The research that the author did was field research using an interdisciplinary approach, namely a sociological juridical approach where the material was obtained from secondary data sources as initial data, then continued with primary data in the field by distributing questionnaires. Then the author also uses a psychological approach to examine the problems raised by qualitative analysis methods. Based on the results of the study, it can be concluded that the fulfillment of the rights and obligations of husband and wife in long-distance married couples has been carried out even though it has not been fully implemented properly.